Development and Validation of New Chromatographic Method for the Determination of Enantiomeric and Diastereomeric Purity of Solifenacin Succinate: An Antimuscarinic Agent. (3rd October 2010) - Landge, Shashikant B.; Jadhav, Sanjay A.; Dahale, Sunil B.; Niphade, Navanath C.; Lakshmi Narayana, Ch.; Gaikwad, Vishwas B.; Mathad, Vijayavitthal T.
Abstract : A new, simple, and rapid stereoselective normal phase-liquid chromatographic (NP-LC) method was developed to separate and quantify the solifenacin succinate and its three stereoisomers. The stereoisomeric separation was achieved on Chiralpak IC (250 × 4.6  mm ID) column. The mobile phase was consisting of n-hexane, ethanol, isopropyl alcohol, and diethylamine in the ratio (60 : 15 : 25 : 0.1, v/v/v/v), and the flow rate was maintained at 1.0 mL min −1 . UV detection was carried out at 220 nm. In addition, chiroptical detection was carried out using laser polarimeter to understand the elution orders. Resolution between all the stereoisomers was not less than 3. Effect of column temperature on resolution between the stereoisomers was studied. The method was validated as per ICH guideline and found to be robust. The proposed NP-LC method was successfully applied to the analysis of commercial formulation. The method could be of use not only for routine evaluation of the quality of solifenacin succinate in bulk drug manufacturing unit but also for detection of impurities in pharmaceutical formulations.